Substantiation of health related power lifting training methodic for univeristies students with muscular skeletal apparatuse affections. - San. Zhen Qiang (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: substantiation of health related power lifting training methodic for universities students, who have disorders of muscular skeletal apparatus. Material: in experimental researches 126 students of 18-24 years' age, having disorders of muscular skeletal apparatus, participated. With the help of testing we registered changes of students' functional, physical and psycho-physiological fitness indicators. Results: optimal correlation of specific and non specific loads was found: 60% of specific and 40% of non specific. It is recommended to follow certain correlation of exercises in easy and complicated conditions: for first year students - 3:2; for second year students - 3:2; for third year - 2:3; for forth year - 2:3; for fifth year students - 1:3. Specific only for power lifting conditions and temps of students' (with muscular skeletal apparatus affections) functional, physical and psycho-physiological fitness improvement were determined. Conclusions: The requirements of the training methodic envisage correction of loads for bringing every indicator on proper level.